Effects of Maternal Diabetes on rat’s Offspring Plasma Ghrelin - Ghasem Ivar; Zahra Ghiravani; Faezeh Rezaei; Somayeh Yousefi; Erfan Lotfi; Mehran Hosseini (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Ghrelin, a natural ligand of the growth hormone secretagogue receptor plays a major role in regulation of appetite, body fat mass, and energy balance in the body. The aim of this study was to evaluate the effects of maternal diabetes on circulatory ghrelin levels in rat newborns. Materials and methods: In this experimental study, female Wistar rats were allocated into diabetic (n=20) and control (n=10) groups and mated with males. After parturition, 16 offspring (8 males) were collected at both postnatal days (P), P7 and P14. The body weight, blood glucose and plasma ghrelin levels were measured. Data were analyzed applying two-way ANOVA using sex and group as the factors in SPSS V22. Results: At both P7 and P14, the body weight of newborns of diabetic mothers (18.49± 0.42g, 22.27± 0.43g respectively) were significantly lower (P<0.0001 each) than those of the control group (22.34± 0.402g, 30.32± 1.45g) while there were no significant differences in blood glucose levels between the two groups. At P7, plasma ghrelin levels showed no significant difference between experimental and control groups, but at P14, experimental group had markedly higher ghrelin levels than that of the control group (29.25± 3.59 pg/ml vs. 14.81± 2.75 pg/ml; P<0.0001). Moreover, at P14, male offspring had significantly higher level of ghrelin than female (29.87± 2.58 pg/ml vs. 22.62±1.68 pg/ml; P<0.0001). Conclusion: Current results clearly demonstrate that diabetes during pregnancy can influence plasma ghrelin levels with male and female offspring responding differently.